Identifying and Analyzing the Portfolio of Iran's Citizen Sports Development Scenario Based on Key Drivers - Mohammad Hasan Abdolahi; Ali Abolhoseini (Research in Sport Management and Marketing)
Purpose: The purpose of this research is to identify the most likely scenario for the development of citizenship sports in the country.Method: According to its nature, the current research is based on a future research approach, which is a survey method in terms of practical purpose. The statistical population of the research includes all experts who have the necessary knowledge and experience in the field of sports. The sampling method is snowball. 16 interviews were conducted with experts. According to the nature of the subject, various techniques and tools were used, such as interviews, expert panels, and questionnaires. In data processing, several techniques are used, including the Delphi technique, cross-effects analysis, and structural analysis, balance of mutual effects, and Mic Mac and Scenario Wizard software to understand the most key drivers and determine the most likely scenarios for the development of citizenship sports in the country Used. Using the structural analysis method (cross-effects) and the use of Mic Mac software, the position of each factor in the obtained system was determined.Results: 10 drivers were identified as the most key future makers in the development of citizenship sports in the country, and by using them, the most likely scenario basket for the development of citizenship sports in the country was obtained.Conclusion: The portfolio of scenarios obtained in this research can be effective as a guide in estimating and forecasting the future of Iranian sports organizations that are related to citizen sports and show a path that will distance them from critical conditions and get closer to the conditions are ideal.